Abela - Doherty, Berlie (London : Andersen Press, 2007)
"Be strong, my Abela" These are the last words of Abela's mother in their HIV/Aids stricken African villige, where it seems that to live or to die, to be sick or to be healthy, is just a matter of chance. It takes all Abela's strenght to survive her uncle Thomas's scheming to get to Europe, but what will be her fate as an illegal immigrant?
Keywords: Adapted sister -- England -- Fiction; Orphans -- Africa -- Fiction